A Method of Analysing Urban Image: Lessons from Kastamonu - Erkan, Nilgun C.; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2010)
This study is about the research method of perception experiment of a settlement. The study displays the role of topography, scale, nature and mode of circulation as environmental peculiarities as well as personal characteristics such as gender, level of education, duration of residency in the perception procedure of the city. The article explains how and to what degree one could benefit from this study of methods and techniques of urban image and mental map researches.
Keywords: Perception; gender differences; Kastamonu; urban image; Architecture